2016
DOI: 10.3847/0004-637x/817/1/8
|View full text |Cite
|
Sign up to set email alerts
|

The Swift GRB Host Galaxy Legacy Survey. Ii. Rest-Frame Near-Ir Luminosity Distribution and Evidence for a Near-Solar Metallicity Threshold

Abstract: We present rest-frame NIR luminosities and stellar masses for a large and uniformly-selected population of GRB host galaxies using deep Spitzer Space Telescope imaging of 119 targets from the Swift GRB Host Galaxy Legacy Survey spanning 0.03 < z < 6.3, and determine the effects of galaxy evolution and chemical enrichment on the mass distribution of the GRB host population across cosmic history. We find a rapid increase in the characteristic NIR host luminosity between z ∼ 0.5 and z ∼ 1.5, but little variation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

46
344
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 205 publications
(395 citation statements)
references
References 105 publications
46
344
3
Order By: Relevance
“…Early studies (see Introduction) on the subject based on incomplete LGRB samples reported a strong preference towards low metallicity values. Lately, however, various studies have indirectly pointed out that this view is only partially correct Krühler et al 2015;Perley et al 2016b). Our results showed that at 0.3 < z < 1 LGRBs preferentially select galaxies of sub-solar metallicities (12 + log O H ∼ 8.4-8.5) and therefore of low stellar masses.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…Early studies (see Introduction) on the subject based on incomplete LGRB samples reported a strong preference towards low metallicity values. Lately, however, various studies have indirectly pointed out that this view is only partially correct Krühler et al 2015;Perley et al 2016b). Our results showed that at 0.3 < z < 1 LGRBs preferentially select galaxies of sub-solar metallicities (12 + log O H ∼ 8.4-8.5) and therefore of low stellar masses.…”
Section: Discussionsupporting
confidence: 54%
“…Our comparisons to VVDS and UltraVista surveys, taking the completeness in brightness, SFR, and M * of the samples into account, indicate that the metallicities of LGRB hosts and star-forming galaxies have similar distributions up to 12 + log O H ∼ 8.4-8.5, after which the already discussed paucity of high-metallicity hosts is observed. This cutoff value, obtained by direct comparison, is similar to the one found in an indirect way in completesample studies by Vergani et al (2015) and Perley et al (2016b). Finally, we note that there are two hosts with very low metallicities in the BAT6 sample with poorly constrained values, which limits their weight in the analysis.…”
Section: Metallicity Distributionsupporting
confidence: 53%
See 3 more Smart Citations